Implementation of Halal Product Assurance Through Halal Certification Among Food and Beverage MSMEs in Cilegon City - Suhroji Adha; Irawan Irawan; Djaka Adiwinata; Mira Nurhikmat; Lia Nurliana; Agnest Mela Dwi Kusmiaty (Universitas Ibn Khladun Bogor, 2025)
This study examines the implementation of halal product assurance through halal certification among food and beverage Micro, Small, and Medium Enterprises (MSMEs) in Cilegon City, Indonesia. The study aims to analyze the extent to which halal certification has been adopted and its role in supporting the development of a sustainable halal ecosystem. A descriptive qualitative approach was employed using interviews, field observations, and document analysis. Data were collected from MSME actors and relevant regulatory sources concerning halal product assurance. The findings indicate that halal certification has become an important instrument for enhancing consumer trust, ensuring product compliance with Islamic principles, and improving business competitiveness. Most leading food and beverage MSMEs in Cilegon have demonstrated awareness of the importance of halal certification as a strategic business asset. However, several challenges remain, including certification costs, limited legal awareness, and administrative constraints faced by small business owners. The study concludes that strengthening collaboration among government agencies, halal certification authorities, and MSMEs is essential to accelerate halal certification adoption and support the growth of Indonesia’s halal industry. The findings contribute to understanding the role of halal certification in fostering business sustainability and consumer confidence in the MSME sector.